2001
DOI: 10.1136/bjsm.35.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Transient forces generated by projectiles on variable quality mouthguards monitored by instrumented impact testing

Abstract: Objectives-(a) To determine the forcetime trace that occurs when a spring mounted simulated upper jaw is impacted; (b) to examine if mouthguards of variable quality have significant influence on such force-time traces; (c) to attempt to relate physical events to the profile of the force-time traces recorded. Methods-A simulated jaw, consisting of ceramic teeth inserted into a hard rubber arch reinforced with a composite jawbone, was fitted with various mouthguards as part of a previous round robin study. A cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…The degree of retention of the MGs was tested classically. 39 Each MG was placed on the maxillary steel model. Then, the steel model was manually turned over.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of retention of the MGs was tested classically. 39 Each MG was placed on the maxillary steel model. Then, the steel model was manually turned over.…”
Section: Methodsmentioning
confidence: 99%
“…39 Each MG was placed on the maxillary steel model. 39 Each MG was placed on the maxillary steel model.…”
Section: Manufacturementioning
confidence: 99%
“…Many recent research studies (4–30) have provided the necessary data to show that there is an effective way to prevent tooth or maxillofacial trauma using a mouthguard (MG) (Tables 1 and 2). However, there are various types of mouthguards including the boil & bite, mass‐produced and marketed to precision‐manufactured, custom‐made types.…”
Section: Previous Studies For Shock Reduction Ability With Mouthguardmentioning
confidence: 99%
“…3,15,17,20,39 While there is a consensus that mouthguards prevent oral injuries, their effectiveness in preventing concussion is either unproven or they have no effect on risks. A number of studies have found no effect of mouthguards on concussion risks.…”
Section: Introductionmentioning
confidence: 99%
“…15,39 This study describes the development of an articulating mandible, compliant TMJ joints, dentition, and instrumentation for the Hybrid III headform. 1 The design and development were conducted by Biokinetics (www.biokinetics.com).…”
Section: Introductionmentioning
confidence: 99%